2021
DOI: 10.1021/jacs.1c07049
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanodots for All-in-One Photocatalytic Hydrogen Generation

Abstract: Carbon nanodots (CNDs) were photochemically altered to produce dihydrogen under light irradiation. Within the complex structure of CNDs, photo-oxidation takes place at citrazinic acid molecular fluorophore sites. Important is the fact that the resulting CND materials have a dual function. On one hand, they absorb light, and on the other hand, they photo-and electrocatalytically produce dihydrogen from water and seawater, without any external photosensitizer or cocatalyst. Record HER activities of 15.15 and 19.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 57 publications
(87 reference statements)
0
45
0
Order By: Relevance
“…The possible clue about the chemical structure of the above red-emitting dyes synthesized from CA and urea has been provided recently by Jana et al 15 They reported extraordinarily high photocatalytic dihydrogen generation (15.15-19.70 mmol (H 2 ) g(catalyst) −1 h −1 ) catalyzed by photochemically altered CDs without any external photosensitizer or cocatalyst. It was inferred that the photooxidation of the CD materials is centered on the citrazinic acid fluorophores, which are present in the CDs and which strongly interact with the carbon dot nanoparticles.…”
Section: Cbmfs In Red-emitting Cdsmentioning
confidence: 99%
See 4 more Smart Citations
“…The possible clue about the chemical structure of the above red-emitting dyes synthesized from CA and urea has been provided recently by Jana et al 15 They reported extraordinarily high photocatalytic dihydrogen generation (15.15-19.70 mmol (H 2 ) g(catalyst) −1 h −1 ) catalyzed by photochemically altered CDs without any external photosensitizer or cocatalyst. It was inferred that the photooxidation of the CD materials is centered on the citrazinic acid fluorophores, which are present in the CDs and which strongly interact with the carbon dot nanoparticles.…”
Section: Cbmfs In Red-emitting Cdsmentioning
confidence: 99%
“…8C). 15 It is important to note that indigoidine (nonfluorescent blue dye) exhibits absorption characteristics similar to red-emitting CDs synthesized from CA and urea. At this moment it is difficult to judge whether some unknown indigoidine derivatives are able to emit light in the red/near-infrared region of the electromagnetic spectrum or not but certainly this might be considered as an interesting starting point for future systematic studies.…”
Section: Cbmfs In Red-emitting Cdsmentioning
confidence: 99%
See 3 more Smart Citations